Singularities of current-voltage characteristics of GaAs films fabricated by pulsed ions ablation; Взаимодействие излучений с твердым телом - Kabyshev A. V. Alexander Vasilievich; Konusov F. V. Fedor Valerievich; Lozhnikov S. N.; Remnev G. E. Gennady Efimovich; Saltymakov M. S. Maksim Sergeevich (Структура и свойства покрытий, 2009)
Заглавие с титульного листа